Modulation-enhanced localization microscopy. (23rd July 2020) - Reymond, Loïc; Huser, Thomas; Ruprecht, Verena; Wieser, Stefan
Abstract: Super-resolution fluorescence microscopy has become a powerful tool in cell biology to observe sub-cellular organization and molecular details below the diffraction limit of light. Super-resolution methods are generally classified into three main concepts: stimulated emission depletion (STED), single molecule localization microscopy (SMLM) and structured illumination microscopy (SIM). Here, we highlight the novel concept of modulation-enhanced localization microscopy (meLM) which we designate as the 4 th super-resolution method. Recently, a series of modulation-enhanced localization microscopy methods have emerged, namely MINFLUX, SIMPLE, SIMFLUX, ModLoc and ROSE. Although meLM combines key ideas from STED, SIM and SMLM, the main concept of meLM relies on a different idea: isolated emitters are localized by measuring their modulated fluorescence intensities in a precisely shifted structured illumination pattern. To position meLM alongside state-of-the-art super-resolution methods we first highlight the basic principles of existing techniques and show which parts of these principles are utilized by the meLM method. We then present the overall novel super-resolution principle of meLM that can theoretically reach unlimited localization precision whenever illumination patterns are translated by an arbitrarily small distance.